Abnormally Small Neuromuscular Junctions in the Extraocular Muscles From Subjects With Idiopathic Nystagmus and Nystagmus Associated With Albinism - McLoon, Linda K.; Willoughby, Christy L.; Anderson, Jill S.; Bothun, Erick D.; Stager, David; Felius, Joost; Lee, Helena; Gottlob, Irene (Investigative ophthalmology & visual science, 2016)
Infantile nystagmus syndrome (INS) is often associated with abnormalities of axonal outgrowth and connectivity. To determine if this manifests in extraocular muscle innervation, specimens from children with idiopathic INS or INS and albinism were examined and compared to normal age-matched control extraocular muscles. Extraocular muscles removed during normal surgery on children with idiopathic INS or INS and albinism were immunostained for neuromuscular junctions, myofiber type, the immature form of the acetylcholine receptor, and brain-derived neurotrophic factor (BDNF) and compared to age-matched controls. Muscles from both the idiopathic INS and INS and albinism groups had neuromuscular junctions that were 35% to 71% smaller based on myofiber area and myofiber perimeter than found in age-matched controls, and this was seen on both fast and slow myosin heavy chain isoform-expressing myofibers (all P < 0.015). Muscles from subjects with INS and albinism showed a 7-fold increase in neuromuscular junction numbers on fast myofibers expressing the immature gamma subunit of the acetylcholine receptor. The extraocular muscles from both INS subgroups showed a significant increase in the number and size of slow myofibers compared to age-matched controls. Brain-derived neurotrophic factor was expressed in control muscle but was virtually absent in the INS muscles. These studies suggest that, relative to the final common pathway, INS is not the same between different patient etiologies. It should be possible to modulate these final common pathway abnormalities, via exogenous application of appropriate drugs, with the hope that this type of treatment may reduce the involuntary oscillatory movements in these children.